Anesthesiology Journal club assessment by means of semantic changes - Vieira,Joaquim Edson (2014)
BACKGROUND AND OBJECTIVES: the interactive approach of a journal club has been described in the medical education literature. The aim of this investigation is to present an assessment of journal club as a tool to address the question whether residents read more and critically. METHODS: this study reports the performance of medical residents in anesthesiology from the Clinics Hospital - University of São Paulo Medical School. All medical residents were invited to answer five questions derived from discussed papers. The answer sheet consisted of an affirmative statement with a Likert type scale (totally disagree-disagree-not sure-agree-totally agree), each related to one of the chosen articles. The results were evaluated by means of item analysis - difficulty index and discrimination power. RESULTS: residents filled one hundred and seventy three evaluations in the months of December 2011 (n = 51), July 2012 (n = 66) and December 2012 (n = 56). The first exam presented all items with straight statement, second and third exams presented mixed items. Separating "totally agree" from "agree" increased the difficulty indices, but did not improve the discrimination power. CONCLUSIONS: the use of a journal club assessment with straight and inverted statements and by means of five points scale for agreement has been shown to increase its item difficulty and discrimination power. This may reflect involvement either with the reading or the discussion during the journal meeting.